2020
DOI: 10.1093/infdis/jiaa266
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Biejia-Ruangan on Fibrosis Regression in Patients With Chronic Hepatitis B Treated With Entecavir: A Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Background Long-term nucleos(t)ide analogue (NA) treatment can reverse liver fibrosis in chronic hepatitis B (CHB), but its effect on fibrosis regression remains limited. Biejia-Ruangan (BR) has been approved in China as an antifibrotic traditional Chinese medicine drug in patients with chronic liver diseases. A multicenter randomized controlled trial aims to evaluate the effect of BR on fibrosis regression in CHB patients treated with NAs. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…Following the inclusion and exclusion criteria in search strategies, a total of 5,017 publications were identified using five databases, of which 1,993 records were removed because of duplicates, 928 were excluded by browsing titles and abstracts, and 2,067 were removed by reading full-text articles. Finally, 29 articles were included in this NMA ( Wang et al, 2004 ; Wang, 2005 ; Zhang et al, 2006 ; Wang et al, 2010 ; Zhang et al, 2016 ; Gu, 2018 ; Li, 2018 ; Xiao and Hu, 2018 ; Xu et al, 2018 ; Zhang et al, 2018 ; Zhao, 2018 ; Chen et al, 2019 ; Liang, 2019 ; Shi, 2019 ; Di and Xia, 2020 ; Li et al, 2020 ; Rong et al, 2020 ; Wang, 2020 ; Yin et al, 2020 ; Yu et al, 2020 ; Zhang, 2020 ; Zhang and Li, 2020 ; Du et al, 2021 ; Huang, 2021 ; Li et al, 2021 ; Wang, 2021 ; Zhang, 2021 ; Zhao, 2021 ; Zhu et al, 2021 ). Detailed information of study selection can be found in Figure 1 , and characteristics of the included RCTs are concluded in Table 1 .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Following the inclusion and exclusion criteria in search strategies, a total of 5,017 publications were identified using five databases, of which 1,993 records were removed because of duplicates, 928 were excluded by browsing titles and abstracts, and 2,067 were removed by reading full-text articles. Finally, 29 articles were included in this NMA ( Wang et al, 2004 ; Wang, 2005 ; Zhang et al, 2006 ; Wang et al, 2010 ; Zhang et al, 2016 ; Gu, 2018 ; Li, 2018 ; Xiao and Hu, 2018 ; Xu et al, 2018 ; Zhang et al, 2018 ; Zhao, 2018 ; Chen et al, 2019 ; Liang, 2019 ; Shi, 2019 ; Di and Xia, 2020 ; Li et al, 2020 ; Rong et al, 2020 ; Wang, 2020 ; Yin et al, 2020 ; Yu et al, 2020 ; Zhang, 2020 ; Zhang and Li, 2020 ; Du et al, 2021 ; Huang, 2021 ; Li et al, 2021 ; Wang, 2021 ; Zhang, 2021 ; Zhao, 2021 ; Zhu et al, 2021 ). Detailed information of study selection can be found in Figure 1 , and characteristics of the included RCTs are concluded in Table 1 .…”
Section: Resultsmentioning
confidence: 93%
“…However, the remaining four ( Wang et al, 2004 ; Zhang et al, 2006 ; Liang, 2019 ; Shi, 2019 ) only reported “randomization,” so they were assessed as “unclear risk.” 2) Allocation concealment: only 3 RCTs ( Wang et al, 2010 ; Xu et al, 2018 ; Rong et al, 2020 ) mentioned it while the rest did not. Therefore, the three trials were regarded as “low risk” while the rest as “unclear risk.” 3) Blinding (including participants and personnel, outcome evaluation): only four publications ( Wang et al, 2004 ; Zhang et al, 2006 ; Wang et al, 2010 ; Rong et al, 2020 ) conducted the blinding method, and 25 ( Wang, 2005 ; Zhang et al, 2016 ; Gu, 2018 ; Li, 2018 ; Xiao and Hu, 2018 ; Xu et al, 2018 ; Zhang et al, 2018 ; Zhao, 2018 ; Chen et al, 2019 ; Liang, 2019 ; Shi, 2019 ; Di and Xia, 2020 ; Li et al, 2020 ; Wang, 2020 ; Yin et al, 2020 ; Yu et al, 2020 ; Zhang, 2020 ; Zhang and Li, 2020 ; Du et al, 2021 ; Huang, 2021 ; Li et al, 2021 ; Wang, 2021 ; Zhang, 2021 ; Zhao, 2021 ; Zhu et al, 2021 ) had insufficient information. Therefore, they were successively estimated as “low risk” and “unclear risk.” 4) Incomplete outcome data: only seven trials ( Wang et al, 2004 ; Wang et al, 2010 ; Zhang et al, 2016 ; Liang, 2019 ; Rong et al, 2020 ; Yin et al, 2020 ; Zhang, 2021 ) described the situation of withdrawal or dropout leading to “low risk,” while the rest did not mention it resulting in “unclear risk.” 5) Selective reporting: all of the included studies were regarded as “low risk” due to the acquirement of the complete implementation scheme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BR exerts its antifibrotic effect via several mechanisms [ 51 53 ]. Recently, a multicenter, randomized, double-blind, placebo-controlled trial showed that addition of BR to nucleoside analog (NAs) in CHB patients with advanced fibrosis or cirrhosis can improve liver fibrosis regression [ 54 ]. Our study found that BR delayed the occurrence of complications of cirrhosis and improved the QOL of nonalcoholic cirrhosis patients without previous OHE or HCC.…”
Section: Discussionmentioning
confidence: 99%
“…All participants provided written informed consent. Data included in this study were obtained from an ongoing randomized controlled clinical trial (NCT01965418) ( 11 ). Briefly, treatment-naive HBV-infected patients who presented to one of participating centers between October 2013 and October 2014 were recruited and randomly assigned in a 1:1 ratio to the treatment group (ETV 0.5 mg/d plus BJRG 2.0 g/time, 3 times daily) or the control group (ETV plus placebo).…”
Section: Methodsmentioning
confidence: 99%